"I Want to Be Trafficked so I Can Migrate!": Cross-Border Movement of North Koreans into China through Brokerage and Smuggling Networks. Issue 1 (March 2018) - Kook, Kyunghee
This article draws on ethnographic fieldwork and in-depth interviews with forty North Korean escapees involved in smuggling and brokerage networks and explores North Korean escapees' cross-border mobility to China. It addresses the complexities of smuggling, showing how the category spans a continuum of actions that might be described as saving or rescuing at one pole, and the kind of exploitation generally termed trafficking at the other. By focusing on the multiple and varied interests and motivations of different actors who assist with North Korean women's migration, I argue that differences among trafficking, smuggling, and migration are constructed rather than essential, and reflect a continued tendency among policy-makers to imagine human mobility through the lens of a fictional opposition between actions that are forced and those that are voluntary. The North Korean women's migratory processes demonstrate the complexities of brokerage and smuggling networks, revealing how they can, but do not necessarily, entail the kind of exploitation generally termed trafficking .